2020
DOI: 10.1016/j.annonc.2020.03.293
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates of response to capmatinib in advanced non-small-cell lung cancer: clinical and biomarker results from a phase I trial

Abstract: Background: Dysregulation of receptor tyrosine kinase MET by various mechanisms occurs in 3%e4% of non-small-cell lung cancer (NSCLC) and is associated with unfavorable prognosis. While MET is a validated drug target in lung cancer, the best biomarker strategy for the enrichment of a susceptible patient population still remains to be defined. Towards this end we analyze here primary data from a phase I dose expansion study of the MET inhibitor capmatinib in patients with advanced MET-dysregulated NSCLC. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 31 publications
3
77
0
1
Order By: Relevance
“…Interestingly, very-high MET mRNA expression closely correlated with MET gene amplification by NGS or FISH and was mutually exclusive with METΔex14. Therefore, it is not surprising that the phenotype of the patients with very-high MET mRNA agrees with the characteristics previously reported in patients with high MET amplification (defined as FISH gene copy number, GCN≥6 or ≥10) [16,17,39,40].…”
Section: Accepted Articlesupporting
confidence: 86%
“…Interestingly, very-high MET mRNA expression closely correlated with MET gene amplification by NGS or FISH and was mutually exclusive with METΔex14. Therefore, it is not surprising that the phenotype of the patients with very-high MET mRNA agrees with the characteristics previously reported in patients with high MET amplification (defined as FISH gene copy number, GCN≥6 or ≥10) [16,17,39,40].…”
Section: Accepted Articlesupporting
confidence: 86%
“…Our mechanistic experiments showed that miR-34a directly interacts with the proto-oncogene MET and attenuates the MET signaling axis by posttranscriptional gene regulation in cancer cells. Activating point mutations of MET and MET ampli cation have been reported in several cancer types, including gastric cancer (65), breast cancer (66), hepatocellular carcinoma (67,68) and non-small cell lung cancer (69,70). MET plays an important role in the occurrence, development, invasion and metastasis of malignant tumors (69,(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…Activating point mutations of MET and MET ampli cation have been reported in several cancer types, including gastric cancer (65), breast cancer (66), hepatocellular carcinoma (67,68) and non-small cell lung cancer (69,70). MET plays an important role in the occurrence, development, invasion and metastasis of malignant tumors (69,(71)(72)(73). While MET is a validated drug target in lung cancer, the best biomarker strategy for enrichment of a susceptible patient population still remained unde ned (69), and its role in HNSCC was not well known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported favorable results with capmatinib in this setting [ 229 ]. With these data, capmatinib obtained the FDA approval in May 2020 for the treatment of patients with advanced NSCLC and a MET exon-14-skipping mutation.…”
Section: Tyrosine Kinase Receptor Inhibitors Developed For Cancer mentioning
confidence: 92%